Vizualizace statistických dat České republiky - Rybnikářová, Hana (Vysoké učení technické v Brně. Fakulta informačních technologií, 2019)
Tato bakalářská práce popisuje návrh a implementaci informačního systému, který vizualizuje statistická data České republiky z oblasti zaměstnanosti, nezaměstnanosti a průměrné mzdy obyvatel. Jeho cílem je přiblížení takových informací studentům, kteří se například rozhodují, jaké povolání zvolit. Data jsou čerpána z Českého statistického úřadu a Ministerstva práce a sociálních věcí a pro vhodnou vizualizaci byl využit nástroj dashboard, který klade důraz na zobrazení všech dat na jednu obrazovku.

This bachelor's thesis describes design and implementation of information system, which visualizes Czech statistical data of employment, unemployment and average salary. The goal is to approach these informations to students who need to determine their future job. Data are taken from Czech statistical office and Ministry of Labour and Social Affairs. For visualization was chosen information dashboard which is visual display of the most important information arranged on a single screen.
Visualization of Czech Statistical Data
Keywords: statistická data; zaměstnanost; nezaměstnanost; mzdy; studenti; vizualizace; dashboard; informační systém; grafy; statistical data; employment; unemployment; salary; students; visualization; dashboard; information system; charts